Heaven on earth a journey through sharia law - Kadri, Sadakat (Bodley Head, 2011)
Almost 1400 years after the Prophet Muhammad first articulated God's law - the sharia - its earthly interpreters are still arguing over what it means. Hardliners reduce it to amputations, veiling, holy war and stonings. Others say that it is humanity's only guarantee of a just society.